A Study of RTLS-based Construction Worker Safety Management System Model - Oh, Jai-woo; Kang, Jin-Kyu (International Journal of Engineering and Technology, 2018)
Background/Objectives: The purpose is to develop a safety management system using location and context information collected from a sensor module for preventing and quickly responding to accidents involving construction workers.Methods/Statistical analysis: In order to develop a safety management system that is suitable for construction sites, there is a need to apply appropriate technologies, taking into consideration the site characteristics. The technologies applied in this research were a sensor module comprised of a device that collects beacon signals, a device that collects data on acceleration and angular velocity, and a wireless networking device for providing the collected information; the gateway technology for transmitting the data on location, tile and acceleration obtained from the sensor module via LoRa communication; real-time fingerprint-based positioning technique; and context-aware technology for recognizing a fall by using the data on tilt and acceleration.Findings: This study was conducted on a safety management system with the aim of preventing accidents on construction sites by providing location-based safety management services to the workers and allowing a speedy response in the event of a fall. To this end, three experiments were carried out: the first experiment was conducted to see whether the alert signal (i.e. vibration) was accurately transmitted inside a danger zone, and it was found that the vibration function of the wearable device worked properly within the designated range; the second experiment checked for errors in the location information of the workers arising from obstacles, and it was found that the alert for the danger zone was properly conveyed within the designated range; and the third experiment checked whether the information of a fall was conveyed quickly upon occurrence, and the results showed that a fall could be identified using the context-aware information from the sensor module and the related algorithm for the information on the fall to be swiftly communicated to the field manager.Improvements/Applications: The findings showed that the real-time location and context-aware information collected from the sensor module can be used to prevent accidents and respond quickly in the event of a fall.Â Â